Zanubrutinib plus salvage chemotherapy for relapsed or refractory diffuse large B-cell lymphoma - Yuan, Xianggui; Li, Xian; Huang, Yurong; Jin, Xueli; Liu, Hui; Zhao, Aiqi; Zhang, Weiping; Qian, Wenbin; Liang, Yun (Frontiers in Immunology, 2022)
Relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL) has poor clinical outcomes when treated with conventional salvage chemotherapy. Monotherapy using zanubrutinib, a selective Bruton's tyrosine kinase (BTK) inhibitor, has achieved modest antitumor effect in R/R DLBCL. Here we aimed to evaluate the efficacy and safety of zanubrutinib plus salvage chemotherapy in R/R DLBCL patients. We retrospectively reviewed R/R DLBCL patients who were administered with zanubrutinib plus salvage chemotherapy in our center between January, 2019 and December, 2021. Targeted panel sequencing of 11 lymphoma-related genes was performed on 8 patients with poor responses to zanubrutinib-based chemotherapy. 27 R/R DLBCL patients were enrolled. Median age at this study was 59 years (range, 15-72). The best overall response rate (ORR) was 74.1% and complete remission rate was 33.3%. With a median follow-up of 11 months (range, 1-17), the median progression-free survival (PFS) was 8.1 months, and the overall survival (OS) was not achieved. The most common grade-3/4 adverse events were neutropenia (70.4%), thrombocytopenia (66.7%), and febrile neutropenia (33.3%). In multivariate analysis, early treatment and overall response after chemotherapy were independent favorable prognostic factors for PFS. Overall response after chemotherapy was an independent favorable factor for OS. Among the 8 patients with poor response to zanubrutinib-based treatment, the majority of patients had NOTCH2 mutations (n=8, 100%) and TP53 mutations (n=7, 87.5%). However, these patients achieved an ORR of 75% at 3 months after CD19-CAR-T cell therapy (including 4 cases of complete remission and 2 cases of partial remission). With a median follow-up of 9 months from CAR-T cell infusion (range, 1-16 months), the median PFS was 14.5 months, and the median OS was not reached. In conclusion, with high efficacy and manageable tolerability, zanubrutinib plus salvage chemotherapy may be a potential treatment option for R/R DLBCL. CAR-T cell therapy may be a priority strategy for these poor responders to BTKi-based treatment.